Effects of pretesting implicit self-determined motivation on behavioral engagement: evidence for the mere measurement effect at the implicit level - Keatley, David A.; Clarke, David D.; Ferguson, Eamonn; Hagger, Martin S. (Frontiers in Psychology, 2014)
Research into individuals’ intended behavior and performance has traditionally adopted explicitly-measured, self-report constructs and outcomes. More recently, research has shown that completing explicit self-report measures of constructs may effect subsequent behavior, termed the ‘mere measurement’ effect. The aim of the present experiment was to investigate whether implicit measures of motivation showed a similar mere measurement effect on subsequent behavior. It may be the case that measuring the implicit systems affects subsequent implicit interventions (e.g., priming), observable on subsequent behaviour. Priming manipulations were also given to participants in order to investigate the interaction between measurement and priming of motivation. Initially, a 2 (IAT: present vs absent) x2 (Prime: autonomous vs absent) and a 2 (IAT: present vs absent) x 2 (Prime: controlled vs. absent) between participants designs were conducted, these were them combined into a 2 (IAT: present vs absent) x3 (Prime: autonomous vs controlled vs absent) between participants design, with attempts at a novel task taken as the outcome measure. Implicit measure completion significantly decreased behavioral engagement. Priming autonomous motivation significantly facilitated, and controlled motivation significantly inhibited performance. Finally, there was a significant implicit measurement x priming interaction, such that priming autonomous motivation only improved performance in the absence of the implicit measure. Overall, this research provides an insight into the effects of implicit measurement and priming of motivation and the combined effect of completing both tasks on behavior.